Penerapan Sistem Informasi Akuntansi dan Pengendalian Internal Persediaan Pada Yoris Bakery Pamekasan - Devi Lestari Pramita Putri; Rr. Anisa Nuraini Primasari (Fakultas Ekonomi Universitas Yos Soedarso, 2020)
In this sophisticated and modern era, a good accounting information system is needed, and good internal control is also needed to minimize things that can harm the company. This is also done for the survival of the company so that the company can run its operations, aka not out of business. The purpose of this study was to determine how the application of accounting information systems and internal control of inventory accounts at the bakery Yoris Bakery Pamekasan. This type of research is qualitative research, using the triangulation method, using data in the form of ordering cycles, inventory cycles, and job descriptions, while the informants are the managers and employees who work at Yoris Bakery on Jalan R. Abd. Aziz and Jalan Trunojoyo. The results showed that the application of accounting information systems in Yoris Bakery has not worked optimally so that it is necessary to use a computerized recording system to avoid recording errors, and the application of internal control is still less effective, it still needs to be increased again.Â Keywords : Accounting Information System; Internal Control; Inventory Account